اثر المناخ التنظيمي علي الولاء التنظيمي للعاملين - عمار, بورقعة; عبد الله, معامرة; نعيمة, بوسيف (جامعة الوادي - University of Eloued, 2023)
"الملخص : تهدف هذه الدراسة إلي التعرف علي أثر المناخ التنظيمي على الولاء التنظيمي للعاملين بمؤسسة عطور الورود ولتحقيق هدف الدراسة تم الاعتماد علي استبانه لعينه عشوائية من العمال بلغ عددها 40 وبعد جمع لاستبانه تم الاعتماد علي برنامج spss لتحليل البيانات واختبار الفرضيات بحيث توصلت الدراسة إلى مجموعة من النتائج أهمها : • تولي مؤسسة عطور الورود بكوينين اهتماما متوسطا بالمناخ التنظيمي . • يتميز الولاء التنظيمي لدى عمال مؤسسة عطور الورود بكوينين بمستوى متوسط • تولى المؤسسة اهتمام مقبولا للمناخ التنظيمى ما نتج عنه ولاء تنظیمی مقبول" "Summary: This study aims to identify the impact of the organizational climate on the organizational loyalty of the employees of the Perfumes of Roses Foundation. To achieve the objective of the study, a questionnaire was relied on for a random sample of 40 workers, and after collecting a questionnaire, the spss program was relied upon to analyze the data and test hypotheses. The study reached a set of results, the most important of which are: • The Perfumes of Roses Foundation in Queenen pays moderate attention to the organizational climate • The organizational loyalty of the workers of the Rose Perfumes Corporation is characterized by two queens at an average level • The institution pays an acceptable attention to the organizational climate, which resulted in an acceptable organizational loyalty to the employees."
Keywords: المناخ التنظيمي، الولاء التنظيمي، الهيكل تنظيمي; climat organisationnel، loyauté organisationnelle